Essays on productivity in Irish agriculture - O'Neill, Suzanne M. (Trinity College (Dublin, Ireland). Department of Economics, 2002)
The focus of this thesis is the measurement of performance in Irish agriculture over the period 1984 to 1998. The methodology applied lies in the broad area of production economics and is located primarily in the microeconometric approach to the estimation of production functions. There is a total of six chapter in the thesis. Chapter 1 is concerned with the policy motivation for the work and describes the data set used in the analysis. Chapter 2 covers the core theoretical foundations underpinning the empirical essays presented in Chapters 3, 4 and 5. It also includes a literature review of production theory, defines the concepts of technical efficiency, technical change and productivity growth. The alternative functional forms and the regularity conditions of the frontier production function are also discussed. The remainder of the chapter concentrates on the estimation of frontier production functions. The starting point, in this section, is a review of cross-sectional models for both deterministic and stochastic frontier production functions followed by the development of panel data models.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin